2021
DOI: 10.1242/jcs.247163
|View full text |Cite
|
Sign up to set email alerts
|

The structural basis of intraflagellar transport at a glance

Abstract: The intraflagellar transport (IFT) system is a remarkable molecular machine used by cells to assemble and maintain the cilium, a long organelle extending from eukaryotic cells that gives rise to motility, sensing and signaling. IFT plays a critical role in building the cilium by shuttling structural components and signaling receptors between the ciliary base and tip. To provide effective transport, IFT-A and IFT-B adaptor protein complexes assemble into highly repetitive polymers, called IFT trains, that are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 107 publications
1
30
0
Order By: Relevance
“…To achieve its function as a retrograde motor for the IFT machinery, the dynein-2 complex must be transported to the ciliary tip as an anterograde IFT cargo. The cryo-EM structure of the human dynein-2 complex, in conjunction with the cryoelectron tomographic structure of Chlamydomonas anterograde IFT trains, suggested that the dynein-2 complex and the IFT-B complex interact with each other via multiple sites 17 , 22 24 . In addition, a study using Chlamydomonas demonstrated that the IFT-B subunit IFT54 directly binds to IFT dynein via its LIC subunit 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve its function as a retrograde motor for the IFT machinery, the dynein-2 complex must be transported to the ciliary tip as an anterograde IFT cargo. The cryo-EM structure of the human dynein-2 complex, in conjunction with the cryoelectron tomographic structure of Chlamydomonas anterograde IFT trains, suggested that the dynein-2 complex and the IFT-B complex interact with each other via multiple sites 17 , 22 24 . In addition, a study using Chlamydomonas demonstrated that the IFT-B subunit IFT54 directly binds to IFT dynein via its LIC subunit 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Our model is largely consistent with the recently clarified cryo-EM structure of the human dynein-2 complex 22 , in which two molecules of DYNC2H1 adopt asymmetric conformations in the tail region, with each DYNC2H1 molecule binding to DYNC2LI1, and either WDR60 or WDR34. Docking of the dynein-2 structure into the anterograde IFT train structure of Chlamydomonas flagella 23 clarified by cryoelectron tomography suggested that each dynein-2 complex spans out multiple IFT-B repeats when it is transported as a cargo of the anterograde IFT train 17 , 22 , 24 . In agreement with the docking model, interactome analyses of WDR60 and WDR34 suggested that dynein-2 interacts with multiple IFT-B subunits 21 .…”
Section: Introductionmentioning
confidence: 99%
“…29 These range from proteins involved in intraflagellar transport (IFT), anterograde and retrograde transport systems required to generate the cilium, transport proteins along its length, and for appropriate signaling; transition zone proteins that form a barrier regulating the protein composition of the cilium; and cargo adaptor proteins. 28,30,31 The cystic kidney disease associated with these syndromic PKD ciliopathies may be due to reduced polycystin-complex (and/or FPC) in the cilium, [32][33][34] analogous to the ER proteostasis defects causing ADPKD/ADPLD. However, the finding from in vivo studies that cilia removal in the kidney in the context of PC1 loss partially rescues PC1-associated cystic disease questions whether there are additional ciliary factors causing or preventing PKD.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, IFT complex B participates in the anterograde transport and it is essential for the assembly and maintenance of cilia. To avoid collision, IFT-A use the A-tubule, and IFT-B move along the B-tubule (36)(37)(38)(39).…”
Section: Intraflagellar Transportmentioning
confidence: 99%